PERAN PKBM DALAM MEMBINA MASYARAKAT PUTUS SEKOLAH DI PKBM MITRA RIAU JAYA CEMERLANG KOTA PEKANBARU - Muh Basori; Desti Irja; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Research it is based on the state of the role of ideal PKBM seen from function. Because such functions is characteristic the base that must be is used to development institutional PKBM as a container learning the community, regarding the role of PKBM according to the community dropping out of school (the community package A) in PKBM Mitra Riau Jaya Cemerlang. Formulation problems research is whether the role of PKBM in build the community of attrition at PKBM Mitra Riau Jaya Cemerlang the city of pekanbaru in good?. The purpose of this research is to find the role of pkbm in build the community of attrition at PKBM Mitra Riau Jaya Cemerlang the city of pekanbaru in good. The population in this research as many as 60 people. Hence sample this research 38 people and 20 people sample the trial with the level of critical 10 percent, the sample used is simple random sampling. An instrument data collection that is chief with 42 a statement and if the trial live 39 a statement valid for in made instrument research. Analysing descriptive analysis quantitative. From scratch answer the results presentation research findings PKBM build role in society is schools in PKBM Mitra Riau Jaya Cemerlang Kota Pekanbaru, Can be concluded the percentage the average (SS+S) 83%. It means the role of pkbm in build the community dropping out of school run well in accordance with the hope the community dropping out of school (the community package A).Kata Kunci: The role of, the role of PKBM , in build the community dropping out of school